The impact of audio visual aids in the improvement of reading comprehension on students of 10th grade (2018)
The aim of this project is to know the impact of audio visual aid in the improvement of reading comprehension on students of 10th grade of a public school in Armenia Quindío. This research was based on the use of pre-reading activities with audiovisual tools as helpers to facilitate the reading comprehension in students. It was carried out in 6 weeks; four of them were used to the interventions with the audiovisuals aids. Each week it was implemented different audio visual strategies such as timelines, videos, slides and songs. In those interventions, teachers took 10 minutes to make the pre-activity and the rest of the class for the text reading and answer the test that was composed of the 10 multiple choice questions. Besides, in the first week, students presented the pre-test (PET) in order to measure their reading comprehension level, also, in the final week, they presented the same test as a post-test in order to compare the results and the effectiveness of the intervention. At the end, students outperformed in the post-test which means audiovisual aids had a positive impact on students’ reading comprehension.